Quantum error-control codes - Ezerman, Martianus Frederic (CRC Press, 2022)
Information is physical. It is sensible to use quantum mechanics as a basis of computation and information processing [19]. Here at the intersection of information theory, computing, and physics, mathematicians and computer scientists must think in terms of the quantum physical realizations of mes- sages. The often philosophical debates among physicists over the nature and interpretations of quantum mechanics shift to harnessing its power for infor- mation processing and testing the theory for completeness. One cannot directly access information stored and processed in massively entangled quantum systems without destroying the content. Turning large- scale quantum computing into practical reality is massively challenging. To start with, it requires techniques for error control that are much more complex than those implemented effectively in classical systems. As a quantum system grows in size and circuit depth, error control becomes ever more important.